Agricultural transformation and market integration in the ASEAN region: Responding to food security and inclusiveness concerns: Training-workshop on rapid value chain assessment - Southeast Asian Regional Center for Graduate Study and Research in Agriculture (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2017)
In preparation for the Training-Workshop on Rapid Value Chain Assessment, the Focal Points & Researchers Meeting was held in the afternoon of 31 October 2017, presided by Dr. Bessie M. Burgos, Program Head for Research and Development of SEARCA. The main objectives of the meeting were to discuss the updates about the project, and to finalize each country’s priority commodity for the national level policy studies (Attachment A). The rationale of the training-workshop and its corresponding expected outputs were likewise discussed during the meeting, while the project deliverables and budget were further clarified. In addition, the role and deliverables of the National Project Steering Committee (NPSC), together with the memoranda of agreement between SEARCA and each focal agency and research institution were also discussed and clarified.